Sonographic and Magnetic Resonance Evaluation of Patent Prolapsed Vitellointestinal Duct in a Neonate: A Case Report - Sharma, Shashi; Sharma, Rohit; Sharma, BB (Journal of Karnali Academy of Health Sciences, 2023)
Omphalomesenteric duct can result in various forms of anomalies due to the failure of its absorption. Various presentations can be in the form of patent vitelline duct, Meckel’s diverticulum, sinus tract, fibrous band, umbilical polyp prolapsing over the umbilicus or enteric fistula. It is important to diagnose these various anomalies in neonates with ultrasonography (USG) and magnetic resonance imaging (MRI) which are radiation free modalities. We present the case of a 20-day-old male baby who was having partial intestinal obstruction, umbilical discharge and slight herniated content from the umbilicus. The neonate underwent USG and MRI studies and was diagnosed with prolapsed vitellointestinal duct. In general, diagnosis of patent prolapsed vitellointestinal duct is difficult on  clinical examination on the first look. In addition to being radiation hazards-free, USG and MRI help in the confirmation of the diagnosis as the anatomical details are well delineated by these modalities. This helps in early management as these types of pathologies can lead to many fatal complications.